CROSS-CULTURAL ADAPTATION AMONG INTERNATIONAL STUDENTS IN THE HOST UNIVERSITY - Muda, Suhani; Mahira, Aliyah Najmi (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This qualitative study explores the factors influencing the cross-cultural adaptation process among international students at a public university in Northern Peninsular Malaysia. The research specifically examines the interplay between students’ predisposition to change and their eventual intercultural transformation. Grounded in Kim’s Cross-Cultural Adaptation Theory, the study frames adaptation as a dynamic, and communication-driven process. The research employed an exploratory qualitative design by conducting in-depth, and semi-structured interviews with ten international students selected via purposive sampling. Data analysis was performed using thematic analysis and was assisted by NVIVO 15 software. Credibility was ensured using member checking and data source triangulation. The findings strongly provide empirical support for the Stress-Adaptation-Growth dynamic, structuring the adaptation into three interconnected stages of input, throughput, and output. The most critical challenge identified was limitations in host communication competence, specifically regarding the management of local accents and operational communication. Successful adaptation was evidenced by the development of functional fitness, which included increased resilience and advanced risk management skills. This research confirms that the adaptation of international students is a dynamic process where internal readiness interacts with and overcomes communicative and environmental challenges. Recommendations are categorised into the need for the host university and future research.